Changes of physical match performance after the COVID-19 lockdown in professional soccer players according to their playing position - Radzimiński, Łukasz; Lorenzo-Martinez, Miguel; Konefał, Marek; Chmura, Paweł; Andrzejewski, Marcin; Jastrzębski, Zbigniew; Padrón-Cabo, Alexis (Biology of Sport, 2022)
The aim of this study was to evaluate the impact of the pandemic lockdown, which included training cessation and home-based training, on physical performance in professional soccer players from the Polish Ekstraklasa according to their playing position. The research was based on 3137 players’ individual match performance observations during the 2019/2020 season divided into before (26 matchdays) and after (11 matchdays) lockdown periods. The data were collected using the computerised multiple-camera optical tracking system TRACAB (ChryronHego VID, New York, NY) with a sampling frequency of 25 Hz. Independently of playing position, a significant (p < 0.001) reduction in season resumption metrics of total distance (-0.9%), jogging (-1.6%), running (-3.4%) and high-speed running (-2.5%), with a contemporaneous increase in walking distance (1.4%), was noted in relation to pre-lockdown performance. A reduction in high-speed running was observed in central defenders (p < 0.05), central midfielders (p < 0.01) and forwards (p < 0.05). No significant decrease in sprinting or maximal running velocity was observed. The COVID-19 lockdown negatively influenced the physical performance in professional soccer players.